‘Sainero’: new variety of xoconostle for the northern region of central Mexico - Gallegos-Vázquez Clemente; Scheinvar, Leia; Silos-Espino Héctor; Fuentes-Hernandez, Alma Delia; Martínez- González César Ramiro; Olalde-Parra, Gabriel; Gallegos-Luevano Nicolás Alejandro (Revista Mexicana de Ciencias Agrícolas, 2018)
From the cultural point of view, xoconostles have been an important factor of economic livelihood of farmers in semi- arid areas of Mexico, which are used as food and traditional medicine. Unfortunately, wild prickly pear are undergoing a process of rapid and irreversible destruction as a result of the opening of land for cultivation and grazing, among other causes. A new horticultural form of the genus Opuntia Miller (Cactaceae), considered as a commonly used variety, found in the municipality of Sain alto, Zacatecas, Mexico, known as xoconostle ‘Sainero’. It was evaluated from 2008 to 2010 and found that its mature cladodes or pads are broad obovate, with 11 to 13 sets of areole, with 4 to 6 spines per areole; blooms once per year and reaches commercial maturity in the month of February of the following year that f lowering occurs. The fruit of ‘Sainero’ is small to medium size (56 cm) and has a broad obovate shape, with the floral scar slightly sunken with an external red color, bright, reddish to whitish walls, broad (11.4 mm, characteristic of xoconostle), acidic (pH 3.1), pink dry to semi-dry and tasteless funiculus, firm, low sugar content (6.3 °Brix) and with few fully developed seeds (137). The average yield on three-year evaluation was 19.16 kg ha-1 and its fruits will remain for more than 12 months on the plant, after the onset of ripening, which gives a comparative advantage over other integrated varieties for commercial production, as Xoconostle Manzano (O. joconostle F.A.C. Weber) grown in the central region of Mexico. This variety counts with the registration number XOC-023-031111 from CNVV-SNICS and is being validated under the conditions of Calera, Zacatecas, in order to establish its adaptability and potential to increase the population for the commercial production of prickly pear in the semiarid region of north central Mexico.